Weighted sharp inequality for vector-valued multilinear commutator of strongly singular integral operator - Zhang, H.; Cai, H. (Український математичний вісник, 2008)
In this paper, a sharp inequality for the vector-valued multilinear commutator of strongly singular integral operator are obtained. By using this inequality, we prove the weighted Lp-norm inequality for the multilinear commutator.